Outcome of an intervention based on adjusting the threshold for hyponatremia in patients undergoing myomectomy: A case control study - Zhijing Yang; Liufang Wang; Youlu Wang; Zhihua Liu; Hui Ai; Wei Pei; Shaomei Xu; Lu Lu; Jie Luo (AFRICAN JOURNAL OF REPRODUCTIVE HEALTH, 2026)
sodium regulation in patients undergoing myomectomy. A retrospective analysis was performed. Patients who underwent myomectomy and received conventional care between March 2014 and March 2019 (n=844) served as the reference group (threshold: 120 mmol/L), while those treated between March 2019 and March 2024 (n=1385) formed the observation group. In the observation group, the hyponatremia critical threshold was raised to 129 mmol/L, alongside targeted interventions including patient education, dynamic sodium monitoring, use of normal saline as the oxytocin solvent, and dietary management. The observation group showed a significantly lower overall incidence of hyponatremia compared with the reference group (21.3% vs. 25.8%, P